«Vergilius non ero, Marsus ero»: la figura di Domizio Marso nell’opera di Marziale (ACME, 2021)
The contribution aims to investigate the presence of Domitius Marsus within Martial’s work, advancing hypotheses about the role of mediation held by the Augustan poet in the history of the Latin epigram. Martial’s corpus often includes significant quotes highlighting Martial’s progressive identification with his predecessor, suggesting that Marsus did not hesitate to look for unique new poetic solutions. As a result, his poetry was highly experimental, in terms of both form and content: alternating between a lighter approach and a more serious, committed one, Marsus represented a clear reference point for Martial, both for his fluid and open interpretation of the epigrammatic genre, as well as for his ability to compose an epigram worthy to fulfil the celebration of power, just like “major” poetry. It could also be argued that Marsus offered a considerable contribution particularly to the development of the epigramma longum, moving away from the callimachean principle of brevitas while remaining faithful to his “minor Muse”.